If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 83(3x + 5) = 7 Reorder the terms: 83(5 + 3x) = 7 (5 * 83 + 3x * 83) = 7 (415 + 249x) = 7 Solving 415 + 249x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-415' to each side of the equation. 415 + -415 + 249x = 7 + -415 Combine like terms: 415 + -415 = 0 0 + 249x = 7 + -415 249x = 7 + -415 Combine like terms: 7 + -415 = -408 249x = -408 Divide each side by '249'. x = -1.638554217 Simplifying x = -1.638554217
| -x+3(-5-2x)=6 | | 5b+3=22-100 | | y=3z+7 | | 6(v+6)-8v=16 | | 11x+16-12=6x-42+8 | | 0+187+x=1.49x | | 3(2x+1)-(x-5)-5(5-2x)=16 | | 18=x+2x | | 5e^8x=1925forx | | 7x+1y=3 | | 8x+28=6x-12 | | 12-3/5*-1/5x=-16 | | 5e^8x=1925 | | V=xlk | | 5b+3=180+90 | | 3ln(5x)-12=9 | | 5b+3=180-90 | | Ln(x+3)=3.2 | | 5b+3=90-180 | | -4=d+35 | | 34x+10=16 | | 5b+3=180 | | 8-3x=6x-10 | | 10(1-6x)-74=6(3-8x) | | 5b+3=90+180 | | (6x+5)(4x+12)=0 | | 2y+14=9y | | 5b+3=90 | | h(t)=-4.9t^2+30.5t+9.1 | | 30+2x=3.50x | | (X+2)(x^2+4x+5)= | | 2x-5=9-X |